2019
DOI: 10.1111/gcbb.12605
|View full text |Cite
|
Sign up to set email alerts
|

A framework for profitability evaluation of agroforestry‐based biofuel value chains: An application to pongamia in India

Abstract: Biofuel production from oilseed trees in small‐scale agroforestry systems is considered as a strategy for energy security, rural development and ecosystem services provision in low‐income countries. However, the economic potential of these systems remains unclear, as profitability studies commonly ignore key methodological issues such as quantitative uncertainty analysis, full accounting for opportunity costs, and inclusion of all value chain actors. This study addresses these methodological shortcomings and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
(102 reference statements)
0
3
0
Order By: Relevance
“…NPV is positive for agroforestry practices in Brazil (Martinelli et al, 2019), and in Acacia decurrens-based agroforestry in the Fagita Lekoma district, Northwestern Ethiopia (Mekonnen et al (2021). However, Dalemans et al (2019) concluded that cultivating Pongamia (Millettia pinnata) agroforestry in southern India is pro table for only small-scale production. Hence, adopting agroforestry practices is useful for enhancing the nancial opportunities of smallholder farmers.…”
Section: The Cash Ow Patterns Of Agroforestry Practicesmentioning
confidence: 99%
“…NPV is positive for agroforestry practices in Brazil (Martinelli et al, 2019), and in Acacia decurrens-based agroforestry in the Fagita Lekoma district, Northwestern Ethiopia (Mekonnen et al (2021). However, Dalemans et al (2019) concluded that cultivating Pongamia (Millettia pinnata) agroforestry in southern India is pro table for only small-scale production. Hence, adopting agroforestry practices is useful for enhancing the nancial opportunities of smallholder farmers.…”
Section: The Cash Ow Patterns Of Agroforestry Practicesmentioning
confidence: 99%
“…Abadi et al (2016) concluded that Pongamia was unlikely to become commercially viable as a biofuel feedstock in Australia, mainly due to uncertainties around yield. Dalemans et al (2019) argued that Pongamia cultivation in India had limited financial potential with biodiesel as the end-product, suggesting that it could only be profitable at a small scale unless there were efforts to optimise mechanization, yields and agroforestry set-ups. Prasad and Singh (2020) found that biodiesel production from Pongamia is an economic viable option in the Pacific Island of Vanua Levu both at a small and large scale.…”
Section: Biodieselmentioning
confidence: 99%
“…However, with lower net returns mainly because during initial years, establishment of Pongamia plantations result in expenditure, without any economic return (Kaushik et al, 2016;Wani et al, 2009). However, although it is argued that the cost of establishment can potentially be met through intercropping during the gestation period of Pongamia plantations (Kaushik et al, 2016), a study evaluating the profitability of Pongamia agroforestry systems using a case study from India, suggested that it has limited financial potential and is only profitable to a sub-set of small-scale farmers in the middle to long term (Dalemans et al, 2019).…”
Section: Agroforestry Potentialmentioning
confidence: 99%